(untitled) (Anuario Español de Derecho Internacional, 2009)
I. INTRODUCTION. II. THE RIGHT TO BE FREE FROM PERSECUTION. III. THE APPLICABILITY OF THE ECHR TO ASYLUM CASES. 3.1. The Right to Life in Asylum Cases. 3.2. The Compatibility of Detention of Asylum Seekers with Article 5. 3.3. The Rights Of Asylum Seekers To Private And Family Life. 3.4. Freedom of Religion and Asylum Seekers. 3.5. Freedom of Association in Asylum Context. 3.6. The Rights Of Asylum Seekers To Marry And To Found A Family. 3.7. The Right Of Asylum Seekers To An Effective Remedy Before A National Authority. 3.8. The Incompatibility Of Discriminatory Measures With Article 14. 3.9. The Right Of Asylum Seekers To Property. IV. FINAL REMARKS.